2020
DOI: 10.1007/s11442-020-1716-9
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of climate change and LULC change on runoff in the Jinsha River Basin

Abstract: The climate change and Land Use/Land Cover (LULC) change both have an important impact on the rainfall-runoff processes. How to quantitatively distinguish and predict the impacts of the above two factors has been a hot spot and frontier issue in the field of hydrology and water resources. In this research, the SWAT (Soil and Water Assessment Tool) model was established for the Jinsha River Basin, and the method of scenarios simulation was used to study the runoff response to climate change and LULC change. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…However, attention should be paid to the fact that these two kinds of land-use types occupy a very small proportion of the whole basin area. The land-use changes in the Jinsha River Basin during the period of 1980-2015 are thoroughly analyzed by Qihui Chen et al [77].…”
Section: Land-use Datamentioning
confidence: 99%
“…However, attention should be paid to the fact that these two kinds of land-use types occupy a very small proportion of the whole basin area. The land-use changes in the Jinsha River Basin during the period of 1980-2015 are thoroughly analyzed by Qihui Chen et al [77].…”
Section: Land-use Datamentioning
confidence: 99%
“…Climate change and LUCC change have essential impacts on precipitation and runoff processes [14,15]. In recent years, a great deal of research has been carried out in China on runoff prediction and attribution analysis in changeable environments [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The changes in LU and CC directly and significantly affect hydrological processes, namely evapotranspiration (ET), groundwater recharge, and streamflow (Chen et al, 2020;Lu et al, 2015;Shrestha et al, 2018;Staal et al, 2020;Venkatesh & Ramesh, 2018). A study by Ghaffari et al (2010) in Northwest Iran reported a significant association between changes in LU and its effect on hydrology.…”
Section: Introductionmentioning
confidence: 99%
“…These changes were triggered by a 0.14% rise in the urban landscape and a reduction in natural forests by 0.7%. It may be noted from earlier studies that most of the research is carried out on past changes to LULC and very few researches studied future/projected LULC changes (Chen et al, 2020;Roy & Inamdar, 2019;Sharannya et al, 2018). A perspective toward future LULC is essential for developing 'what-if' scenarios and can support LU planning and policy.…”
Section: Introductionmentioning
confidence: 99%